CHARACTERISTIC COMPARISION OF CLARK OXYGEN SENSORS MADE FROM DIFFERENT ELECTRODE MATERIALS - Hà, Vũ Thị Thu; Nữ, Đặng Thị Tố (Vietnam Journal of Science and Technology, 2012)
SUMMARYClark oxygen sensors made from different materials for cathodic electrode have been fabricated successfully. Their behaviors in terms of response time, reproducibility, stability were investigated. The obtained results indicated  that studied Clark oxygen sensors using gold single microelectrode, array  gold microelectrode, platinum and conventional gold, provide response time: 6s, 10s, 18s and 23s  with their residual currents: negligible, 31nA,  63nA and 62nA respectively. There is a good  agreement  between DO values measured by studied sensors and  Winkler titration. The investigation also showed that among studied sensors, the sensor made of gold microelectrode behaves as the  best sensor for further application.